Prevalence of impostor syndrome among undergraduate and postgraduate medical students – A cross-sectional study - Shivani Agrawal; Sundhareshwaran Chandrasekaran; Tajwar Yasmeen; Sanjay Kumar; Shishir Kumar (Journal of Indira Gandhi Institute of Medical Sciences)
Background: Impostor syndrome (IS), a psychological phenomenon, has gained prominence, especially among doctors and other high achievers. It involves a sense of inadequacy and fear of being exposed as a fraud despite notable accomplishments. This study aims to estimate the prevalence of IS among medical students. Understanding this phenomenon’s impact on medical education and professional development is crucial for effective support and intervention strategies. Methodology: This cross-sectional study was conducted among 280 undergraduate (UG) and postgraduate (PG) medical students. Data were collected using a standardized questionnaire on IS, the Clance Impostor Phenomenon Questionnaire. The data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) software version 26. Results: 61.07% were male (n = 171) and 38.93% were female (n = 109). 51.07% (n = 143) were PG students, whereas 48.93% (n = 137) were UG students. Mean Clance score of the participants was 42.70 ± 15.866 (indicating overall moderate IS). 55.00% (154) had few/no IS, and 45.00% (126) had some form of IS. Specifically, 26.43% (74) experienced moderate IS, 13.57% (38) reported frequent experiences, and 5.00% (14) described intense experiences of IS. Conclusion: The study reveals a notable prevalence of IS among medical students, with a substantial proportion experiencing moderate-to-intense symptoms. These findings underscore the importance of addressing psychological well-being and self-perception in medical education to support students’ professional development effectively.